ANALISIS NILAI PENDIDIKAN AGAMA ISLAM DALAM TRADISI NYADRAN: Studi di Desa Pringu Bululawang Malang - Qomari, Nur; Roihanah (Jurnal Penelitian Ilmiah INTAJ, 2024)
The dynamic development of the times has an impact on traditional ceremonies which have Islamic meaning in them. Where Nyadran is a Javanese culture with the acculturation of Hinduism and Islam as a guide to the happiness of human life. The nyadran tradition is a tradition of the people of Pringu Village as an activity of respecting ancestors through prayers from generation to generation which is carried out before the month of Muharram (Asyuro') or precisely in the month of Dzulhijah. Nyadran is held on Monday Pahing or Legi. Where in this writing the focus is on religious and cultural acculturation as a form of social fabric in society. Research was carried out through interviews, documentation and observation using data analysis techniques starting from presentation, conclusions and verification. The researchers concluded that (1) The Nyadran ritual procession in Pringu Village, Bululawang District, was carried out like other areas, including flower sowing, khatm Al-Qur'an and eating together; (2) The Islamic values ​​include gratitude, worship, and aqidah.